MODELING OF TURNAROUND OPERATIONS FOR NEXT GENERATION SPACE TRANSPORTATION ARCHITECTURES - Ruiz-Torres, Alex J; Zapata, Edgar; Cowen, Marcella (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper presents an approach to space transportation turnaround operations modeling using knowledge based complexity functions. This project is of signiticant relevance to the field of industrial engineering as it deals with knowledge based estimation of processing operations based on the design characteristics of an extremely complex product. The modeling approach uses experts knowledge to predict the ground cycle time and costs of a new concept launch vehicle by functions that estimate the complexity and reliability of the system based on its design characteristics. The operational requirements include the interactions between the launch vehicle and its ground infrastructure: the spaceport. Finally, the paper discusses the implementation of the modeling concept into a tool called Architecture Assessment Tool enhanced (AA Te) used byNASA and its contractors.